Successful Diagnosis of Epithelial Thymic Cancer Case Using EBUS-TBNA - Tammy Issa MD; Rupam Sharma MD; Shatha Aboaid MD; Rahul D. Polineni MD; Ayham Aboeed MD (SAGE Publishing, 2022)
Mediastinal masses are relatively uncommon. Surgical approach is often needed to diagnose mediastinal masses. Using endobronchial ultrasound transbronchial needle aspiration (EBUS-TBNA) toward approaching a mediastinal mass has yet to be established. Here, we present a case of successful diagnosis of thymic cancer with the use of EBUS-TBNA.